2015
DOI: 10.1007/s12639-015-0651-7
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the prevalence of strongyles species in working donkeys in North-West of Iran

Abstract: Faecal samples for detection of gastrointestinal parasites were collected from 60 donkeys from 6 villages in Marand, North-West of Iran. Faecal samples of 2 donkeys (3.33 %) were negative for parasite eggs. 48 positive donkeys (81.66 %) were infected with a single parasite type, 9 (15.51 %) and 1 (1.66 %) of donkeys had multiple infections with two and three parasites, respectively. The highest prevalence and intensity rate belonged to small strongyles. The overall prevalence of intestinal parasites eggs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…eggs,” Strongylus spp. larvae,” “cyathostomins eggs” and “cyathostomins larvae.” Infection rates between 4.4 and 69.2% in horses [ 35 – 37 , 114 – 127 ], 65.4 and 96.4% in four studies on donkeys [ 36 , 117 , 128 , 129 ] and 80% in the only study on mules [ 117 ] have been reported.…”
Section: Helminthosesmentioning
confidence: 99%
See 1 more Smart Citation
“…eggs,” Strongylus spp. larvae,” “cyathostomins eggs” and “cyathostomins larvae.” Infection rates between 4.4 and 69.2% in horses [ 35 – 37 , 114 – 127 ], 65.4 and 96.4% in four studies on donkeys [ 36 , 117 , 128 , 129 ] and 80% in the only study on mules [ 117 ] have been reported.…”
Section: Helminthosesmentioning
confidence: 99%
“…Infection of human patients with T. axei has also been reported [ 171 ]. Adult nematodes have been isolated from horses [ 115 ] and donkeys [ 128 , 131 ]. There are also some reports on detection of eggs of T. axei in coproscopic examinations in horses [ 125 , 172 ], donkeys and mules [ 172 ].…”
Section: Helminthosesmentioning
confidence: 99%
“…The disease is characterized by fever, anaemia, red urine, jaundice, oedema, weight loss and even death in equine (Mahmoud et al., 2016). On the other hand, strongylosis is caused by several nematodes, often referred to as the small and large strongyles (Tavassoli, Yamchi, & Hajipour, 2016). They are frequently responsible not only for poor health, but also for gastrointestinal dysfunction, including colic, and infection with some such as acute larval cyathostomosis may be fatal (Love, Murphy, & Mellor, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This review also revealed that most (but not all [Eslami, Bokai, & Tabatabai, 2005; Hossien, Bokaei, & Roudgari, 2008; Khedri, Radfar, Borji, & Azizzadeh, 2014; Razmi, Abedi, & Yaghfoori, 2016]) of the studies failed to observed a significant association between prevalence of parasites and age of the animals (Armand, Solhjoo, Shabani‐Kordshooli, Davami, & Sadeghi, 2016; Eslami et al., 2005; Ghadrdan‐Mashhadi, Hamidienjat, & Alizadehnia, 2013; Gharekhani, Tavoosidana, & Naderisefat, 2013; Malekifard et al., 2014; Tajik, Mirshahi, Razmi, & Mohammadi, 2010; Tavalla et al., 2015; Tavassoli, Sodagar‐Skandarabadi, & Soltanalinejad, 2007). Also, most (but not all [Khedri et al., 2014]) of the studies failed to observe any significant association between the prevalence of parasites and sex (Hossien et al., 2008; Hosseini et al., 2009; Hosseini et al., 2011; Raeghi, Akaberi, & Sedeghi, 2011; Rasuli, Khodadadi, Sadagiyani, Moradpoor, & Salmanzadeh, 2012; Gharekhani et al., 2013; Ghahfarrokhi, Ahmadi, Shahraki, & Azizi, 2014; Hassanpour & Nematollahi 2014; Mcallister, 2014; Tavassoli et al., 2016). And lastly, most (but not all [Hossien et al., 2008; Khedri et al., 2014]) of the studies failed to observe any significant association between the prevalence of parasites and season (Armand et al., 2016; Tavassoli et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Today, equine strongylosis is highly prevalent worldwide (3, 21, and 22) and poses a serious threat to the populations of horses and donkeys (4,10). In Iran, in Marand, an area adjacent to the Chehrabad Archeological Site, the prevalence rate of strongyle nematodes among 58 donkeys was 100% (23,24). The occurrence of strongyles among the equids does not pose a public health threat; however, very few reports on human infections with Bertiella studeri, a member of the Anoplocephalidae family, are available (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%